Terpenoid compositions and botanical origins of Late Cretaceous and Miocene amber from China. - Gongle Shi (Public Library of Science (PLoS), 2014)
The terpenoid compositions of the Late Cretaceous Xixia amber from Central China and the middle Miocene Zhangpu amber from Southeast China were analyzed by gas chromatography-mass spectrometry (GC-MS) to elucidate their botanical origins. The Xixia amber is characterized by sesquiterpenoids, abietane and phyllocladane type diterpenoids, but lacks phenolic abietanes and labdane derivatives. The molecular compositions indicate that the Xixia amber is most likely contributed by the conifer family Araucariaceae, which is today distributed primarily in the Southern Hemisphere, but widely occurred in the Northern Hemisphere during the Mesozoic according to paleobotanical evidence. The middle Miocene Zhangpu amber is characterized by amyrin and amyrone-based triterpenoids and cadalene-based sesquiterpenoids. It is considered derived from the tropical angiosperm family Dipterocarpaceae based on these compounds and the co-occurring fossil winged fruits of the family in Zhangpu. This provides new evidence for the occurrence of a dipterocarp forest in the middle Miocene of Southeast China. It is the first detailed biomarker study for amber from East Asia.